The Latin American forage seed market: recent developments and future opportunities - Gallo Caro, Irieleth; Enciso, Karen; Burkart, Stefan; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2021)
Cattle farming in the Latin American (LA) lower tropics is characterised by extensive production systems with low productivity levels and negative environmental impacts. Given the sector’s economic and social importance, we need to understand the dynamics involved with the adoption of sustainable production technologies (e.g. improved forages). Among the limiting factors in this regard is forage seed availability. Our study has two objectives: i) analysing behaviour and potential of the LA forage seed market; and ii) identifying limitations/opportunities in forage seed commercialisation. Information was obtained in 2020-2021 through literature review, database analysis on import and export of forage seeds, and in-depth interviews with 13 principal LA forage seed suppliers. Through a descriptive market behaviour analysis, the characteristics and functioning of the forage seed market were detailed for several LA countries (i.e. involved actors, market evolution and expansion limitations, informal market and future prospects). The market potential was defined from a sustainable intensification perspective, that includes the areas currently used for cattle production that require improvement strategies (productivity increases and environmental impact decreases). Our results show that the forage seed market, in the recent decade, followed particular dynamics occurring in the analysed countries. Major fluctuations have occurred in most countries, due to e.g. regulatory policies and taxes for seed commercialisation. Some countries (e.g. Bolivia) show a continuous increase resulting from formalisation processes strengthening forage technology adoption. Changes in seed preferences towards new varieties occurred in some countries, while in others, traditionally marketed varieties maintained their market shares. Among the limiting factors for improved forage seed adoption, cultural aspects, scarce collaboration among actors (research/development institutions, seed producers/distributors), slow bureaucratic processes and constant seed price variations (associated with a dependence on the Brazilian market dynamics) were identified as crucial. All studied countries present high market potential for improved forage seeds. Whether it can be exhausted or not is subject to each country’s specific dynamics that could encourage (e.g. conservation policies) or limit (e.g. land tenure insecurity) sustainable intensification processes. Our results help policy-/decision-makers in public policy formulation aimed at forage seed market development and serve seed producers/distributors for increasing market penetration.